Public health policies to encourage healthy eating habits: recent perspectives - Gorski MT; Roberto CA (Dove Medical Press, 2015)
Mary T Gorski,1 Christina A Roberto2,3 1Interfaculty Initiative in Health Policy, Harvard University, Cambridge, 2Department of Social and Behavioral Sciences, 3Department of Nutrition, Harvard TH Chan School of Public Health, Boston, MA, USA Abstract: There is an urgent need to address unhealthy dietary patterns at the population level. Poor diet and physical inactivity are key drivers of the obesity pandemic, and they are among the leading causes of preventable death and disability in nearly every country in the world. As countries grapple with the growing obesity prevalence, many innovative policy options to reduce overeating and improve diet quality remain largely unexplored. We describe recent trends in eating habits and consequences for public health, vulnerabilities to unhealthy eating, and the role for public health policies. We reviewed recent public health policies to promote healthier diet patterns, including mandates, restrictions, economic incentives, marketing limits, information provision, and environmental defaults. Keywords: food policy, diet, obesity, public health